PENGUNGKAPAN INTELLECTUAL CAPITAL PADA MANAGEMENT LETTER DAN NILAI PERUSAHAAN - Dyna Rachmawati; The, Louis Maria (Universitas Kristen Krida Wacana, 2024)
The purpose of this research is to examine the effect of disclosure of intellectual capital on the value of manufacturing sector companies listed on the Indonesia Stock Exchange in 2019-2021. This study uses management letter as a source to collect the disclosure of intellectual capital. This study used a data sample for the 2019-2021 period of 294 manufacturing firm years which were determined by the purposive sampling method. The data analysis technique used is a multiple linear regression. The results of the study show that the disclosure of intellectual capital has a positive and significant effect on firm value. The decomposition disclosure of intellectual capital reveal that the environmental capital component has a positive and significant effect while the components of human capital, structural capital and relational capital have no effect on firm value. The control variables in this study, namely profitability and firm size, have no effect on firm value. The implication of this study is the disclosure of intellectual capital in the management letter has the information content. Investors consider disclosure of green intellectual capital management letter important. It shows the management commitment in implementing intellectual capital. Keywords: environmental capital, firm value, intellectual capital, human capital, relational capital, structural capital